2018
DOI: 10.1002/acp.3484
|View full text |Cite
|
Sign up to set email alerts
|

Using network science to analyze concept maps of psychology undergraduates

Abstract: Network science is an emerging area of complexity science that uses mathematical techniques to study complex systems and could represent a new way of quantifying and investigating the internal structure of domain-specific knowledge as approximated by students' concept maps. Students enrolled in introductory psychology constructed concept maps to represent their understanding of a psychology chapter.Concept networks were constructed based on the concept maps generated by students. Network analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…These patterns highlight differences in the specific expertise of individuals. Although the relationship between conceptual associations and domain specific expertise has not been fully explored yet (Aitchison, 2012), a few pioneering approaches have recently established how the structure of semantic networks can be predictive of students' performance in quizzes (Siew, 2019;Tyumeneva, Kapuza & Vergeles, 2017). The further exploration of a link between network structure and domain expertise represents an interesting future research direction for forma mentis networks, also in terms of investigating the effects of shared knowledge and of prior-knowledge over learning outcomes in the sense of Koponen, Kokkonen & Nousiainen (2017).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns highlight differences in the specific expertise of individuals. Although the relationship between conceptual associations and domain specific expertise has not been fully explored yet (Aitchison, 2012), a few pioneering approaches have recently established how the structure of semantic networks can be predictive of students' performance in quizzes (Siew, 2019;Tyumeneva, Kapuza & Vergeles, 2017). The further exploration of a link between network structure and domain expertise represents an interesting future research direction for forma mentis networks, also in terms of investigating the effects of shared knowledge and of prior-knowledge over learning outcomes in the sense of Koponen, Kokkonen & Nousiainen (2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent approaches have constructed association networks at the level of individuals Siew, 2018) and even reported how individualized free association networks were predictive of creativity levels or knowledge mastery (Siew, 2018). With larger sample sizes and a more substantive free association task (leading to denser networks), building forma mentis networks for the individuals represents an exciting research direction for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Psycholinguistic evidence has shown that the associative structure of the mental lexicon influences language processes such as word learning (Hills & Siew, 2018;Stella, 2019;Stella, Beckage, & Brede, 2017) and processing (De Deyne, Navarro, & Storms, 2013;De Deyne, Navarro, Perfors, Brysbaert, & Storms, 2018;Kenett, Levi, Anaki, & Faust, 2017;Steyvers & Tenenbaum, 2005). This strong link between mental lexicon structure and language usage promoted the use of network models for a variety of processes such as the discovery of writing styles from word co-occurrences in texts (Amancio, 2015) or predicting the creativity of individuals (Kenett, Anaki, & Faust, 2014;Kenett et al, 2018), their curiosity (Zurn & Bassett, 2018), their openness to new experience (Christensen, Kenett, Cotter, Beaty, & Silvia, 2018), their expertise in a given domain (Siew, 2018;Valenzuela Castellanos, Pérez Villalobos, Bustos, & Salcedo Lagos, 2018) and their perceived anxiety toward a topic (Siew, McCartney, & FORMA MENTIS NETWORKS IN STEM 6 Vitevitch, 2019). Forma mentis networks rely on the framework of cognitive network science to represent the associative and emotional structure of concepts in the mental lexicon.…”
Section: Introductionmentioning
confidence: 99%
“…These studies analyzed the concept maps produced by teachers-in-training and high school students as networks to identify central, important concepts in their conceptual structure (Koponen & Nousiainen, 2018), detect meso-level structures that reflect thematic communities in a domain (Lommi & Koponen, 2019), and compare the overall network structure of experts against that of novices (Koponen & Pehkonen, 2010). Recent work by Siew (2019b) showed that the overall network structure of concept maps is a significant predictor of quiz scores and could serve as one indicator of successful learning and retention of content. Lydon-Staley and colleagues (Lydon-Staley, Zhou, Blevins, Zurn, & Bassett, 2019) showed that the different search strategies that people adopted while navigating Wikipedia resulted in different knowledge networks (i.e., Wikipedia pages that were connected based on the sequence in which they were being navigated).…”
Section: Learning and The Development Of Conceptual Knowledgementioning
confidence: 99%